A frictionless model of job flows and the Beveridge Curve - Christopher Phillip Reicher (Kiel Institute for the World Economy (IfW), 2010)
The Diamond-Mortensen-Pissarides search and matching model is the workhorse of labor macro, but it has difficulty in simultaneously matching the cyclical behavior of job loss and vacancies when taken to the data. By completely ignoring frictions in job creation and focusing instead on firm-level heterogeneity, one can match the cyclical behavior of job flows and vacancies relatively well. In particular, one can generate a Beveridge Curve which looks much like the real Beveridge Curve, and one can replicate the approximately equal contributions of job creation and destruction to the cycle. Focusing on heterogeneity rather than on hiring costs seems to give an improved picture of hiring activity over the cycle.
Keywords: J62; J21; 330; Arbeitsmarkttheorie; Arbeitsmobilität; Arbeitsuche; Matching; Arbeitsnachfrage; Unternehmen; Beveridge-Kurve; Theorie